More than DeQi: Spatial Patterns of Acupuncture-Induced Bodily Sensations - Jung, Won-Mo; Shim, Woosun; Lee, Taehyung; Park, Hi-Joon; Ryu, Yeonhee; Beissner, Florian; Chae, Younbyoung (Frontiers in Neuroscience, 2016)
Acupuncture uses needles to stimulate certain parts of the body, inducing a specific sensation, termed DeQi, which many regard as essential for acupuncture's therapeutic effect. Here, we used the newly developed tool, bodily sensation mapping, to investigate the spatial configuration of acupuncture-induced sensations throughout the body. Twenty-five participants randomly received acupuncture stimulation or tactile stimulation using a von Frey filament at four different acuoints (HT7, PC6, ST36, and SP10) on the left side of the body. Subjects evaluated the characteristics of DeQi sensations and marked the areas of induced sensations on a body outline. We compared the psychophysical responses of DeQi sensations and visualized the spatial patterns of these sensations using statistical parametric mapping. We found greater intensity of DeQi sensations following acupuncture stimulation compared with tactile stimulation, with relatively small differences among the four acupoints. The sensation maps exhibited similar spatial patterns for acupuncture and tactile stimulation in the areas close to the stimulated sites. However, acupuncture was associated with additional sensations in areas remote from the stimulated sites. This study demonstrates that acupuncture stimulation produces greater DeQi sensations than tactile stimulation and results in the spreading of sensations to areas remote from the stimulus sites. Investigating the spatial patterns of acupuncture-induced sensations may be crucial for understanding the underlying mechanisms of acupuncture.